Lysosomal alkalization to potentiate eradication of intra-osteoblastic Staphylococcus aureus in the bone and joint infection setting. (January 2022) - Abad, Lélia; Chauvelot, Pierre; Audoux, Estelle; Andre, Camille; Josse, Jérôme; Dupieux, Céline; Lustig, Sébastien; Ferry, Tristan; Verhoeven, Paul O.; Diot, Alan; Laurent, Frédéric; Valour, Florent
Abstract: Objectives: Beyond intracellular penetration, acidic lysosomal pH might affect the intracellular activity of some antimicrobials. This study evaluated the ability of lysosomotropic alkalizing agents to potentiate the antimicrobial eradication of an intra-osteoblastic Staphylococcus aureus reservoir in the setting of bone and joint infection (BJI). Methods: MICs of 16 anti-staphylococcal molecules active against methicillin-sensitive S. aureus (MSSA) were evaluated at pH 5 and pH 7. Additionally, the lysosomal alkalizing potential (spectrofluorometry) and cytotoxicity (MTT assay) of hydroxychloroquine, amantadine and ammonium chloride were assessed. The results led to further investigation of clindamycin, cotrimoxazole, daptomycin and levofloxacin—alone or in combination with hydroxychloroquine—in an in vitro model of osteoblast infection. The impact of hydroxychloroquine on autophagy was finally investigated using Western blot detection of two autophagic flux indicators, the LC3 membrane protein and the SQSTM1 cargo protein. Results: Daptomycin, cotrimoxazole, clindamycin and levofloxacin alone significantly decreased the intracellular staphylococcal reservoir (5.12 log10  CFU/100 000 cells) by 0.14 (95%CI 0.01–0.34), 0.25 (95%CI 0.12–0.43), 0.16 (95%CI 0.004–0.39) and 1.18 (95%CI 1.04–1.38) log10  CFU/100 000 cells, respectively (p < 10 −3 ). Adding hydroxychloroquine (20 mg/L) increased intralysosomal pH from 4.8 to 7, and concomitantly the inoculum of each antimicrobial was reduced by 0.50 (95%CI 0.30–0.84), 0.73 (95%CI 0.59–0.96), 0.59 (95%CI 0.46–0.78) and 1.8 (95%CI 1.66–2.1) log10  CFU/100 000 cells, respectively (p < 10 −4 ). Cellular levels of LC3II and SQSTM1 showed that hydroxychloroquine has direct activity on the autophagic flux, fostering the eradication of intracellular S. aureus by antimicrobials. Conclusion: At high concentrations, hydroxychloroquine used as an adjuvant to antimicrobials improves eradication of an S. aureus intra-osteoblastic reservoir in our in vitro cell infection model. These findings advocate further in vivo evaluation of alkalization efficacy and tolerance in S. aureus BJI.